Esther - Rich, Richard; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : Nest Family Entertainment, 2005)
The story of the young Queen Esther, one of the Bible's most courageous women.
Includes Read-A-Long Sing-A-Long DVD.
Includes Resource & Activity Book.
"Premium website accessible through DVD-ROM"--Container.
"NEST complete learning system."
DVD ; 2-channel Dolby digital surround sound.
In English with optional Spanish language track and optional English or Spanish subtitles.
Keywords: Esther, -- Queen of Persia -- Juvenile films; Bible stories -- Juvenile films; Animated films; Children's films